The outcomes of Gastrointestinal manifestations in Covid-19 infection on mortality, disease severity and hospitalization period. A mini-review - Daghman, Daad Jamil; Ahmad, Abdullah Muad Sayed; Dayoub, Nour Adnan (Journal of medical and pharmaceutical sciences, 2022)
Introduction: Since the documentation of the first case of Covid-19 disease in Dec 2019 in China the world is suffering under the weight of this pandemic which applied a heavy burden on public health. Although covid-19 infection is dangerous for causing Acute respiratory distress syndrome and its sequelae however an important number of cases manifest with gastrointestinal symptoms whether before or during illness. We will try in this mini-review to highlight the prevalence of gastrointestinal symptoms in Covid-19 patients and its impact on disease prognosis. Methods: We reviewed 43 research articles, 24 met selection criteria while the remaining articles were screened for information regarding any gastrointestinal manifestations. Conclusion: Some cases were found to have GI manifestations without pulmonary disease. Most reports showed GI manifestations have no significant association with worse outcomes but are associated with longer hospitalization period. Further studies will help determine the impact of GI manifestations on disease course.